Kerjasama Preservasi Koleksi Langka Perpustakaan Pusat Survei Geologi dengan Perpustakaan Nasional - Ramadhan, Farhan Iswana Putra; Prijana, Prijana (Institut Agama Islam Negeri Salatiga, 2023)
In a nation, libraries serve as centers for the management and preservation of knowledge, representing the intellectual wealth and cultural heritage of the nation. Therefore, library collections, especially rare manuscripts, require special attention due to their historical, cultural, and essential knowledge value. One of the libraries in Indonesia that possesses rare manuscripts is Perpustakaan Pusat Survei Geologi. Perpustakaan Pusat Survei Geologi collaborates with The National Library of Indonesia Perpustakaan Nasional to manage and preserve these rare manuscripts. This research is conducted to conduct an in-depth study of the outcomes and forms of the preservation collaboration of rare manuscripts between Perpustakaan Pusat Survei Geologi and Perpustakaan Nasional, including its processes, benefits, challenges, and its impact on the community or readers, Perpustakaan Pusat Survei Geologi, and Perpustakaan Nasional. The research employs a descriptive qualitative approach, using data collection techniques such as observation and interviews. The research findings reveal that the preservation collaboration activities between Perpustakaan Pusat Survei Geologi and Perpustakan Nasional are considered to run smoothly. Through this collaborative program, approximately 60 titles of rare manuscripts available at Perpustakaan Pusat Survei Geologi have been successfully digitized. The benefits of this collaboration are evident for both parties, although the impact on users is perceived as not yet having a significant effect.